Library Management in Building Learning Societies in Primary School Muhammadiyah, Islamic Boarding School Wali Songo Ngabar, and Madrasah Tsanawiyah Kembang Sawit - A.D. Saputro, M.S. Rachmandhani, Z. K. Prasetyo, S. Arifin, A. Ariyanto (International Journal of Advanced Science and Technology, 2020)
This article aims to find differences about management library in building learning societies in Primary School (SD) Muhammadiyah 1 Ponorogo, Islamic Boarding School Wali Songo Ngabar, MTSN Kembang Sawit Madiun. The applied of library management is very interesting to study. So that, it can be an example to other schools in building learning societies in the school environment. The good cooperation between library, teacher, and headmaster has been succeeded to deliver SD Muhammadiyah 1 Ponorogo to achieve achievement at the International level. This research by using a qualitative research method by type multi sites study. This research has found the differences in the library management which have been implemented by the three schools, that is SD Muhammadiyah 1 Ponorogohas implemented function of library management based of barcodes technology with a type Linear 1D Barcodes and literacy program in building learning societies in the school. Islamic Boarding School Wali Songo Ngabar Ponorogo has not implemented library management based on barcode technology and has not implemented literacy program in building learning societies in the school. While MTSN Kembang Sawit Madiun has not implemented library management based on a barcodes technology and has not implemented literacy program in building learning societies in the school.Keywords: function management, library school, building learning societies.